History of art in Japan - Tsuji, Nobuo, 1932-; Rousmaniere, Nicole Coolidge, 1961- (New York: Columbia University Press, 2018)
"In this book the leading authority on Japanese art history tells the fascinating story of the country's exceptional cultural heritage. Tsuji Nobuo sheds light on how Japan has nurtured distinctive aesthetics, prominent artists, and movements that have achieved global influence and popularity. The History of Art in Japan discusses works ranging from the Jōmon period to contemporary art, from earthenware figurines in 13,000 BCE to manga, anime, and modern subcultures"--
"This book originally appeared in Japanese as Nihon bijutsu no rekishi (Tokyo: University of Tokyo Press, 2005). First English edition published 2018 by University of Tokyo Press."
Includes bibliographical references and index.
Keywords: Art, Japanese